2018
DOI: 10.1007/s13665-018-0203-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bacterial Transmission in Bronchiectasis Outpatient Clinics

Abstract: Purpose of ReviewThe purpose of this review is to discuss the risk of bacterial cross-infection for bronchiectasis patients in the outpatient setting. Cross-infection has primarily been a matter of concern in cystic fibrosis (CF). There is considerable evidence of transmission of pathogens between CF patients, and this has led to guideline recommendations advocating strict segregation policies. Guidelines in bronchiectasis do not specifically address the issue of cross-infection. If cross-infection is prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Incidentally, we found two study participants with bronchiectasis who were high producers of H. influenzae cough aerosols, 26 a common respiratory pathogen of patients with bronchiectasis and COPD. [36][37][38][39][40] Whilst H. influenzae cross-infection is not thought to occur in patients with bronchiectasis, 18 it has been recently reported in a single study of patients with CF, 41 although it is presently unclear if aerosol transmission plays a role in H. influenzae acquisition. Our study reported one non-expectorating participant with COPD who produced cough aerosols containing C. koseri and Achromobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidentally, we found two study participants with bronchiectasis who were high producers of H. influenzae cough aerosols, 26 a common respiratory pathogen of patients with bronchiectasis and COPD. [36][37][38][39][40] Whilst H. influenzae cross-infection is not thought to occur in patients with bronchiectasis, 18 it has been recently reported in a single study of patients with CF, 41 although it is presently unclear if aerosol transmission plays a role in H. influenzae acquisition. Our study reported one non-expectorating participant with COPD who produced cough aerosols containing C. koseri and Achromobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…13 Yet, unlike CF, cross-infection with P. aeruginosa is reported to be uncommon in patients with bronchiectasis and COPD. [14][15][16][17][18][19][20] Although the evidence for crossinfection is infrequent in non-CF suppurative lung diseases, 15,16 the transmission mechanism of possible person-to-person transmission events has not been studied previously. Therefore, we sought to determine if (i) patients with bronchiectasis or COPD can produce cough aerosols containing P. aeruginosa and (ii) if respiratory infections with shared P. aeruginosa strains occur in patients with bronchiectasis and COPD attending a centre that is co-located with a large adult CF centre.…”
Section: Summary At a Glancementioning
confidence: 99%
See 1 more Smart Citation
“…[10] Furthermore Mitchelmore et al analysed Pa in a non-segregated NCFB population (n=46) and detected 3 cases of cross-infection in patients who shared a waiting room and lung function room. [11] The British Thoracic Society guidelines state that for NCFB there is no evidence of Pa transmissibility and that segregation is not routinely required [1] while the EMBARC Patient Advisory Group and the European Reference Network (ERN-Lung) Bronchiectasis Network recommend that currently there is insufficient evidence to advise segregation. [12] We present two family case studies, all of whom have NCFB, in which household Pa transmission does not occur, despite a significant contact history amongst the paired subjects.…”
mentioning
confidence: 99%
“…[11] Transfer of respiratory pathogens can occur by either direct or indirect contact transmission, droplet transmission or airborne transmission. [12] It is advisable that patients with suspected or confirmed pulmonary TB be isolated in a single room with negative pressure and en suite facilities. [13] This is, however, not always possible.…”
mentioning
confidence: 99%